Association between sleep deprivation and fertility - a literature review - Adriana Dukacz; Anna Konarska; Anna Machowiak; Barbara Ufnalska; Justyna Lisiecka; Mateusz Janik; Michał Nowak; Joanna Rychlewska-Duda; Wojciech Firlej; Artur Fabijański (Journal of Education, Health and Sport)
Infertility gained increasing importance throughout our life period in this fast pacing world as increasingly more couples struggle to conceive. Taking into account the cost of fertility treatment there is a good strategy to look into less high-priced options on increasing conception possibilities. In this article we are going to focus on one of them which is sleep. Sleeping hygiene is neglected by many of us as only 8% of polish population rate their sleeping as satisfactory. There are primary matters for instance regular sleep hours, sustaining a healthy diet to make a tremendous change in our mental and as well reproductive health. In the male population deprived sleep is blamed for lower sperm motility, as well as concentration, total count. There is a probability that Leydig cells function and count, cortisol secretion and testosterone levels can be affected but for now we have to conduct more research to rule it out or confirm. For women on the other hand sleep depravation produces a huge hormonal dysregulation. Temporarily the impact of sleep depravation is being inconsistent about estradiol, prolactin and melatonin. This article presents a meticulously collected date which shows the connection between sleep and punctuate need for further research.